Disruptive business model development of telkomsel m2m through cross-industry innovation - Permana, Addy; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2016)
Abstract - The main challenge for mobile telecom operators is how to innovate their products and services to get sustainability growth. With revenue of legacy voice and SMS tend to decline and increasing demand for broadband data services. Telecom operators must develop the right products based on broadband technology to keep growth and compete. Telkomsel as the largest mobile operator in Indonesia is undertaking a business transformation. Developing solutions Machine to Machine (M2M) is one of the masterpiece programs. Telkomsel M2M business is designed to trigger the growth of the digital ecosystem in Indonesia which further strengthen the foundation of digital service Telkomsel. By using the framework of research in the form of external environment analysis (PEST, Porter’s five forces), internal environment analysis (Value Chain and VRIO), then continued in the form of business strategy. Further, create Cross-industry innovation to create business models. Telkomsel M2M Business model will be developed based on business models canvas. Development of the business model is also expected to boost the company's earnings significantly, especially as a new generator in digital business. Keywords: Business Model, Telecommunication, M2M